Analisis Role-Model Guru PAI Dalam Peningkatan Pembelajaran Agama Islam Dalam Perspektif Psikologi Pendidikan Islam : Studi di SDN Bhayangkara Yogyakarta - Wahyu Anis Amanullah Amanullah; Wantini Wantini; Ahmad Muhammad Diponegoro (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2023)
Psychology and Islamic education play a role in the world of education, both in learning and in teaching. In everyday life, we find that children's religious behavior is essentially obtained by imitating. The purpose of this study was to analyze the role models of PAI teachers in enhancing Islamic learning from the perspective of Islamic educational psychology. The research approach uses qualitative research. This research was conducted at SDN Bhayangkara. The subjects of this research are teachers and students. Data collection techniques using observation, interviews, and documentation Data analysis uses data reduction, data display, and data conclusion verification. The results of the study allow it to be concluded that this role model is a positive method in children's religious education. In the process of learning the Islamic religion, students will see and imitate the behavior of their teacher. The application of educational psychology in Islamic learning is through strengthening and punishing. strengthening, for example, with praise, grades, or prizes for students as a reward for their achievements. While the punishment is memorizing or replacing the teacher in front of delivering PAI learning material, Through the application of reinforcement and punishment, it is hoped that it can increase student motivation in learning PAI.